2020
DOI: 10.1590/1981-6723.03420
|View full text |Cite
|
Sign up to set email alerts
|

Flow behavior of cocoa pulp powder containing maltodextrin

Abstract: This study aimed to evaluate the influence of maltodextrin addition on the flow properties of cocoa pulp powder obtained by spray and freeze drying. Cocoa pulp samples received 15% and 30% (m m-1) maltodextrin DE20. Two drying methods were used, spray and freeze drying. Powder morphology was evaluated through scanning electron microscopy (SEM). Wall friction angle, bulk density and tapped density were determined. Carr index (CI), Hausner ratio (HR) and flow index (FI) were used to evaluate powder flow. The par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…The smoothest surfaces can occur due to the presence of low‐molecular‐weight sugars, which act as plasticizers, reducing surface shrinkage during drying in the spray dryer (Loksuwan, 2007). Cavalcante et al (2017) and Ribeiro et al (2020) reported smooth surfaces in particles of powders of different fruit pulps obtained in spray drying using maltodextrin as carrier. Furthermore, Mohammed et al (2021) studied drying aids mixtures in the encapsulating Nigella sativa oil by spray drying and observed that samples with maltodextrin in their mixture resulted in smoother particles than the mixture without it.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The smoothest surfaces can occur due to the presence of low‐molecular‐weight sugars, which act as plasticizers, reducing surface shrinkage during drying in the spray dryer (Loksuwan, 2007). Cavalcante et al (2017) and Ribeiro et al (2020) reported smooth surfaces in particles of powders of different fruit pulps obtained in spray drying using maltodextrin as carrier. Furthermore, Mohammed et al (2021) studied drying aids mixtures in the encapsulating Nigella sativa oil by spray drying and observed that samples with maltodextrin in their mixture resulted in smoother particles than the mixture without it.…”
Section: Resultsmentioning
confidence: 99%
“…In the work of Ribeiro et al (2020), the cocoa pulp powder had CI of 24.88 and HR of 1.33, using 30% (m/m) maltodextrin. Zea et al (2013) found CI of 27.2 and HR of 1.37 for guava pulp powder and CI of 34.9 and HR of 1.53 for pitaya pulp powder, using 10% (m/m) maltodextrin in both cases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations